NEAT1_2 functions as a competing endogenous RNA to regulate ATAD2 expression by sponging microRNA-106b-5p in papillary thyroid cancer - Sun, Wei (Cell Death Dis, 2018)
Nuclear paraspeckle assembly transcript 1 (NEAT1), a long non-coding RNA (lncRNA), is a core structural component of paraspeckles and is essential for paraspeckle formation. NEAT1 comprises two different isoforms: NEAT1_1 (3.7 kb) and NEAT1_2 (23 kb). Recently, NEAT1 has been shown to have oncogenic roles and to facilitate tumorigenesis in various human cancers. However, the function of NEAT1 in papillary thyroid cancer (PTC) is not well understood. The relative expression levels of NEAT1_2, ATPase family AAA domain-containing protein 2 (ATAD2), and microRNA-106b-5p (miR-106b-5p) were assessed via quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR). Four PTC cell lines were used to detect the relative expression of NEAT1_2. The effects of NEAT1_2 on PTC cells were studied by RNA interference approaches in vitro. The effects of NEAT1_2 on downstream proteins were detected by western blotting. The underlying mechanism was clarified by a rescue experiment, and three dual-luciferase reporter assays. NEAT1_2 expression was markedly increased in PTC tissues and the PTC cell lines (K1 and TPC1). The relative expression level of NEAT1_2 was positively associated with TNM stage and tumor size. NEAT1_2 knockdown led to a significant inhibition of growth and metastasis, and induced apoptosis in PTC cells. Knockdown of NEAT1_2 significantly inhibited malignant biological behavior by downregulating the oncogene ATAD2. In addition, NEAT1_2 could act as a competing endogenous RNA to regulate the expression of ATAD2 through downregulating miR-106b-5p. Taken together, our results indicated that NEAT1_2 is overexpressed in PTC. NEAT1_2 could function as a competing endogenous RNA to regulate ATAD2 expression by sponging miR-106b-5p in PTC. Targeting NEAT1_2 could be a promising therapeutic strategy for patients with PTC.